Web Presence and Features of Library Websites Webpages of NIRF Ranked Pharmacy Institutes of South India: An Evaluative Study - S, Madhu; B.U., Kannappanavar (DESIDOC Journal of Library & Information Technology, 2024)
The study focuses on conducting a web content analysis of 28 library websites and webpages of NIRF-ranked South Indian Pharmacy Institutes of India. Data collection utilised the observation and survey methods of the concerned websites and webpages. The analysis reveals that two libraries (7.14%) utilise open-source content management systems (WordPress and Webs) to develop their dedicated library websites. A large majority (96.43%) of libraries provided information about the library, printed books and journals, and copyright statements on their websites/webpages. Information regarding subscribed e-journals and e-books was found on 24 (85.71%) libraries' websites. Additionally, fifty percent of libraries offered information relevant to ILL/document delivery, remote access, and reprographic services as core services. E-learning platforms such as CourseWare, Edx, Swayam Prabha, NPTEL, and Swayam were mentioned on 12 (42.86%) libraries' websites, while eight (28.57%) libraries provided plagiarism checking facility. The study also highlights that only a few libraries are familiar with implementing Web 2.0 technologies. The overall results found that even the top scoring websites/webpages have only fifty percent of the web contents present based on the predefined criteria. The findings of this study can assist librarians and webmasters in restructuring their library websites with user-friendly designs and features to provide essential content about their libraries, collections and services.